Structured content and data management-enhancing acceleration in drug development through efficiency in data exchange - Jill Beierle; Marquerita Algorri; Marisol Cortés; Nina S. Cauchon; Andrew Lennard; J. Paul Kirwan; Shirley Oghamian; Michael J. Abernathy (SpringerOpen, 2023)
Abstract Innovation in pharmaceutical therapeutics is critical for the treatment of serious diseases with unmet medical need. To accelerate the approval of these innovative treatments, regulatory agencies throughout the world are increasingly adopting the use of expedited pathways and collaborative regulatory reviews. These pathways are primarily driven by promising clinical results but become challenging for Chemistry, Manufacturing, and Controls (CMC) information in regulatory submissions. Condensed and shifting timelines present constraints that require new approaches to the management of regulatory filings. This article emphasizes technological advances that have the potential to tackle the underlying inefficiencies in the regulatory filing eco-system. Structured content and data management (SCDM) is highlighted as a foundation for technologies that can ease the burden on both sponsors and regulators by streamlining data usage in regulatory submissions. Re-mapping of information technology infrastructure will improve the usability of data by moving away from document-based filings towards electronic data libraries. Although the inefficiencies of the current regulatory filing eco-system are more evident for products that are filed using expedited pathways, it is envisioned that the more widespread adoption of SCDM, across standard filing and review processes, will improve overall efficiency and speed in the compilation and review of regulatory submissions.